Reality And Factors of Influence on The Development of Arabic Language Education Curriculum at SDNU Kencong Jember - Siti Rumania; Nuryani Nuryani; Adib Nurwahid (Journal of Arabic Language Teaching, 2023)
The strategic role of the curriculum will trigger the efficiency and effectiveness of learning. The curriculum directs all learning activities while essential to realizing a quality educational institution. Seeing the orientation and role of the curriculum, curricular changes can occur at any time by existing needs. Social changes in society and the development of Science and technology should be immediately responded to in curriculum development at every level of Education. This type of qualitative research understands the phenomenon experienced by research subjects, such as action, thought, motivation, and others. At the same time, the researchers used a descriptive approach. The results show that the reality of Arabic language education today should be an excellent opportunity to create brighter prospects for enthusiasts and activists of the Arabic language in the future. Scientific epistemology and curriculum must always be addressed and developed to plan the curriculum to produce a wide range of curriculum specifics.